Against the Stream: lowering the age of sexual consent. (20th July 2018) - Graham, Philip
Abstract : Lowering the legal age of sexual consent would decriminalise a large number of 'underage' young people engaging in sexual intercourse. The arguments against such a change in the law are summarised and shown to lack validity. Declaration of interest: None.